Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11090-006-9002-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of Ca0.8 Sr0.2 TiO3 for Plasma Activation of CO2

Abstract: Despite a large interest in plasma-assisted catalytic technology (PACT), very little has been reported about the catalytic effects of different dielectric barriers on a dielectric barrier discharge (DBD) reaction. In the present study, Ca 0.8 Sr 0.2 TiO 3 , that possesses a high permittivity, was prepared by liquid phase sintering and used as a dielectric barrier in a DBD reactor to break CO 2 . The mechanical and dielectric properties of Ca 0.8 Sr 0.2 TiO 3 were greatly enhanced by adding 0.5 wt.% Li 2 Si 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…5 Moreover, it was employed to break down CO 2 efficiently by a DBD plasma. 6,7 Comparative studies showed that the CO 2 reactivity increased with increasing relative permittivity of the barrier materials and both of them followed the sequence Ca 1−x Sr x TiO 3 ӷ alumina ͑Al 2 O 3 ͒ ജ silica glass ͑SiO 2 ͒. 6,7 However, our recent in-depth study showed an existence of an optimum permittivity for the barrier materials to generate dense and strong current pulses.…”
Section: Investigation Of Dielectric Barrier Discharge Dependence On mentioning
confidence: 82%
See 1 more Smart Citation
“…5 Moreover, it was employed to break down CO 2 efficiently by a DBD plasma. 6,7 Comparative studies showed that the CO 2 reactivity increased with increasing relative permittivity of the barrier materials and both of them followed the sequence Ca 1−x Sr x TiO 3 ӷ alumina ͑Al 2 O 3 ͒ ജ silica glass ͑SiO 2 ͒. 6,7 However, our recent in-depth study showed an existence of an optimum permittivity for the barrier materials to generate dense and strong current pulses.…”
Section: Investigation Of Dielectric Barrier Discharge Dependence On mentioning
confidence: 82%
“…4 We have developed a dielectric barrier material, Ca 1−x Sr x TiO 3 with Li 2 Si 2 O 5 additive, which has a high relative density, a high dielectric constant, and a high dielectric strength. [5][6][7] This ceramic was used as dielectric barriers to ignite dense and strong plasma with high energy. 5 Moreover, it was employed to break down CO 2 efficiently by a DBD plasma.…”
Section: Investigation Of Dielectric Barrier Discharge Dependence On mentioning
confidence: 99%
“…However, since C in the CO 2 exhibits the highest oxidation state, the CO 2 itself is chemically stable, and the standard Gibbs free energy (DG h ) of CO 2 is -394.39 kJ mol -1 (Dean 1998), which means CO 2 is a kind of inert molecule and is difficult for activation. To react with other molecules, the kinetics inertia and thermodynamics energy barrier should be overcome, which generally requires employing high temperature (Balucan and Dlugogorski 2012), high pressure (Liu et al 2013c) and using catalysts (Drees et al 2012;Ashley and O'Hare 2013), including coordinating activation (Huff et al 2012;Vogt et al 2012), Lewis acidbase synergistic activation (Ashley et al 2009;Mömming et al 2009), photoelectric activation (Jing et al 2013), biological enzyme catalytic activation (Kumar et al 2010) and plasma activation (Li et al 2006), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Suib et al [16][17][18] have conducted a series of study on CO 2 decomposition in AC glow discharge reactors, and investigated the various influence factors such as metal catalysts, discharge parameters and additional gases. Li et al [19][20][21][22] have used Ca x Sr (1-x) TiO 3 as barrier materials in the decomposition of CO 2 in dielectric barrier discharge (DBD) plasma, and investigated the relation between the microdischarges and the permittivity of the barrier materials. It was found that Ca 0.8 Sr 0.2 TiO 3 with 0.5 wt% Li 2 Si 2 O 5 as dielectric barrier is optimum to obtain a steady discharge state and an efficient decomposition of CO 2 .…”
Section: Introductionmentioning
confidence: 99%